2016
DOI: 10.1007/s11764-016-0557-0
|View full text |Cite
|
Sign up to set email alerts
|

Is a behavioral treatment for urinary incontinence beneficial to prostate cancer survivors as a follow-up care?

Abstract: Seeking PFME-based treatment is crucial for long-term urinary health outcomes even if present leakage is minor or financial challenge is a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Although these data support the efficacy of our rehabilitation program, it is necessary to evaluate the long‐term effects, because continuing exercises is necessary after rehabilitation to maintain continence, as confirmed by the literature 13,18 …”
Section: Rationalesupporting
confidence: 54%
See 1 more Smart Citation
“…Although these data support the efficacy of our rehabilitation program, it is necessary to evaluate the long‐term effects, because continuing exercises is necessary after rehabilitation to maintain continence, as confirmed by the literature 13,18 …”
Section: Rationalesupporting
confidence: 54%
“…17 Although these data support the efficacy of our rehabilitation program, it is necessary to evaluate the long-term effects, because continuing exercises is necessary after rehabilitation to maintain continence, as confirmed by the literature. 13,18 T A B L E 1 PFMT rehabilitation program Morning (Figure 1b) Slightly more difficult than exercise 1, due to the action of gravity. When the exercise is performed correctly, the patient should find it more difficult with his legs spread (the position with legs closed ensures additional sustain to the pelvic organs, with better contrast to gravity).…”
Section: Rationalementioning
confidence: 99%
“…In the Zhang and etc. (2017) study it was seen that an early diagnosis of urinary incontinence or minor incontinence together with an education in pelvic exercises had a positive effect on the patients [31].…”
Section: Discussion Of Features Of the Patients And Caregivers' Socia...mentioning
confidence: 97%
“…Given EMG assessment is invasive in a group setting, it may have been useful to use it in the one-to-one session with the CNS to assess the effectiveness of the individuals’ exercises. Studies of PFME in men with PCa have focused mainly on the surgical setting and have shown that pelvic floor muscle exercises pre- and post-treatment can improve symptom outcomes [ 41 ] and this evidence is reflected in NICE UK [ 42 ] prostate cancer guidelines. Studies show that men who continue to have LUTS after radiotherapy have significant reductions in quality-of-life [ 43 ].…”
Section: Discussionmentioning
confidence: 99%